Efikasi Diri dalam Penggunaan Komputer dan Persepsi Kemudahan Penggunaan sebagai Prediktor Stres Teknologi - Limaheluw, Melda; Prapunoto, Susana; Kristianingsih, Sri Aryanti (Bulletin of Counseling and Psychotherapy, 2025)
The use of technology such as computers has become a primary necessity across various employment sectors. The increasing intensity of technology use often presents challenges to users, one of which is technostress. Technostress can negatively impact individual well-being and productivity, both in the workplace and in personal life. This study aims to examine the extent to which computer self-efficacy and perceived ease of use can predict levels of technostress among workers. The population of this study consists of 120 employees who use computers in the fields of administration, operational management, and information and communication technology (ICT) within the Klasis Taniwel. The sampling technique employed was purposive sampling. Data were collected using three instruments: the Technostress Creators Scale to measure technostress, the Computer Self-Efficacy Scale to measure self-efficacy in computer use, and a scale to measure Perceived Ease of Use. Data analysis was conducted quantitatively using a correlational design with multiple linear regression. The findings indicate that both computer self-efficacy and perceived ease of use, whether simultaneously or individually, significantly predict technostress.